2014
DOI: 10.1242/jcs.164723
|View full text |Cite
|
Sign up to set email alerts
|

The tumor suppressor Nf2 regulates corpus callosum development by inhibiting the transcriptional coactivator Yap

Abstract: The corpus callosum connects cerebral hemispheres and is the largest axon tract in the mammalian brain. Callosal malformations are among the most common congenital brain anomalies and are associated with a wide range of neuropsychological deficits. Crossing of the midline by callosal axons relies on a proper midline environment that harbors guidepost cells emitting guidance cues to instruct callosal axon navigation. Little is known about what controls the formation of the midline environment. We find that two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…However, whether schwannomin contributes to SCHIP1-mediated axon outgrowth and guidance is uncertain since SCHIP1 and schwannomin expression patterns are different during brain development (Huynh et al, 1996). In addition, Nf2 F/F ;Emx1-cre mice do not present AC defects but instead CC agenesis, which does not result from a lack of schwannomin in callosal neurons or their progenitors but in midline neural progenitor cells (Lavado et al, 2014). Schwannomin appeared to regulate guidance cue expression, whereas SCHIP1 does not and is directly involved in axon development.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, whether schwannomin contributes to SCHIP1-mediated axon outgrowth and guidance is uncertain since SCHIP1 and schwannomin expression patterns are different during brain development (Huynh et al, 1996). In addition, Nf2 F/F ;Emx1-cre mice do not present AC defects but instead CC agenesis, which does not result from a lack of schwannomin in callosal neurons or their progenitors but in midline neural progenitor cells (Lavado et al, 2014). Schwannomin appeared to regulate guidance cue expression, whereas SCHIP1 does not and is directly involved in axon development.…”
Section: Discussionmentioning
confidence: 91%
“…Schwannomin has been shown to play roles in axon growth and guidance (Lavado et al, 2014;Schulz et al, 2010;Yamauchi et al, 2008). However, whether schwannomin contributes to SCHIP1-mediated axon outgrowth and guidance is uncertain since SCHIP1 and schwannomin expression patterns are different during brain development (Huynh et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that NF2 can nonautonomously affect axon guidance in the developing mouse brain (Lavado et al 2014). This guidance mechanism occurs through regulation of Slit2 mRNA levels, suggesting a transcriptional role of NF2 (Lavado et al 2014).…”
Section: Slt-1 Mutations Enhance Aqr Defects Of Nfm-1 (Lq132)mentioning
confidence: 91%
“…NF2/Merlin is involved in signaling pathways involving hippo, mTOR, and PI3K-Akt (Zhao et al 2007;Striedinger et al 2008;James et al 2009;Okada et al 2009). Additionally, NF2 is involved in nervous system maintenance, corpus callosum development, and axon guidance (Schulz et al 2013(Schulz et al , 2014Lavado et al 2014). In corpus callosum development, NF2 inhibits the hippo pathway component Yap.…”
mentioning
confidence: 99%
See 1 more Smart Citation